2020
DOI: 10.1029/2019jb017823
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Structure of the Antarctic Upper Mantle Imaged with Adjoint Tomography

Abstract: The upper mantle and transition zone beneath Antarctica and the surrounding oceans are among the poorest‐imaged regions of the Earth's interior. Over the last 15 years, several large broadband regional seismic arrays have been deployed, as have new permanent seismic stations. Using data from 297 Antarctic and 26 additional seismic stations south of ~40°S, we image the seismic structure of the upper mantle and transition zone using adjoint tomography. Over the course of 20 iterations, we utilize phase observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
122
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(129 citation statements)
references
References 189 publications
(432 reference statements)
7
122
0
Order By: Relevance
“…Although there are controversies on this feature, the areas from Mount Erebus to Mount Melbourne are generally considered to share the same geodynamic process due to the continuity of slow upper mantle velocity under this region (e.g., Kobayashi & Zhao, 2004; Gupta et al, 2009). Our results and resolution tests (Figures 2 and S5) indicate that the low‐V zone is constrained to the shallow mantle (~150–250 km depths), consistent with a recent tomographic result (Lloyd et al, 2019). If lower‐mantle upwelling occurs beneath the TR, a strong low‐V zone rather than a weak low‐V zone should be imaged at greater depths (Figure S5d), which is different from our result (Figures 2b and 2f).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although there are controversies on this feature, the areas from Mount Erebus to Mount Melbourne are generally considered to share the same geodynamic process due to the continuity of slow upper mantle velocity under this region (e.g., Kobayashi & Zhao, 2004; Gupta et al, 2009). Our results and resolution tests (Figures 2 and S5) indicate that the low‐V zone is constrained to the shallow mantle (~150–250 km depths), consistent with a recent tomographic result (Lloyd et al, 2019). If lower‐mantle upwelling occurs beneath the TR, a strong low‐V zone rather than a weak low‐V zone should be imaged at greater depths (Figure S5d), which is different from our result (Figures 2b and 2f).…”
Section: Discussionsupporting
confidence: 90%
“…The high‐V zone detected at greater depths can also obstruct heat transfer from the warm asthenosphere. In addition, a recent waveform tomography does not show a clear low‐V zone to the west of the WSB (Lloyd et al, 2019), suggesting that there is no heat source in the west. A magnetic and gravity study revealed that the whole WSB is underlain by a rifted continental crust (Ferraccioli et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…We do not consider the effects of lateral heterogeneity in the solid Earth structure as our study area is small, and three are unlikely to be significant lateral variations within the area covered by the GPS sites. However, Barker et al (2001) suggest there is a lateral variation in the solid Earth structure along the length of the Peninsula and this has been further supported by recent seismic tomographic analysis (Lloyd et al 2019). Previous experiments in this region (e.g.…”
Section: Discussionmentioning
confidence: 82%
“…(b) A map view of Vs at 80 km beneath the surface of the solid Earth. The red contour highlights the boundary of the model of Shen, Wiens, Stern, et al (2018) and Shen, Wiens, Anandakrishnan, et al (2018) embedded in the model of Lloyd et al (2019). Seismic stations are shown as red triangles and black circles by the two studies, respectively.…”
Section: Introductionmentioning
confidence: 99%